DETEKSI INTEGRITAS GENOMIK PISANG HASIL IRADIASI IN VITRO BERDASARKAN PENANDA MIKROSATELIT - Megia, Rita; Ratna, Nina Ratna (UI Scholars Hub, 2010)
Genomic Integrity Detection of In Vitro Irradiated Banana Using Microsatellite Marker. The research aims to detect genomic integrity of in vitro irradiated banana using microsatellite marker. These studies were done on banana cv. Pisang Mas irradiated by 15 Gy of gamma ray. The DNA was isolated from each accesion following Dixie. Amplification of DNA products were done by Perkin Elmer Gene Amp PCR 2400 using ten primers, and then electroforesis in agarose 1%. Finally a vertical polyacrylamide gel electroforesis was run and the products were visualized by silver staining. The result shown that among the primers tested, eight primers produced clear, discrete, and reproducible bands. Number of DNA band exhibited ranging from one to two, following the ploidy level of pisang Mas which is a diploid banana cultivar (AA). One band suggest homozygote allele while two bands showed heterozygote allele. Out of eight primers, six primers produced different allele among irradiated, in vitro, and in vivo control plant. Meanwhile, for the other two primers the allele were monomorph for all the accessions examined. Genomic modification was observed at all irradiated plants. The modification can happened at zygosity of certain allele that may change from heterozygote to homozygote or vice versa. While modification in allele size that underlying genomic instability could be caused by several genetic events such as deletion, insertion, and amplification of nucleotides.